The energetic storm particle events of 3 November 2021 - Chiappetta, Federica; Laurenza, Monica; Lepreti, Fabio; Benella, Simone; Consolini, Giuseppe; Marcucci, Maria Federica (Frontiers in Astronomy and Space Sciences, 2023)
Observations of energetic particles at interplanetary shocks are important to study acceleration mechanisms and their connection with magnetohydrodynamic turbulence. Energetic storm particle (ESP) events are increases in proton fluxes that occur locally at the passage time of interplanetary shocks. These events are more dangerous when they are superimposed on the solar energetic particles (SEPs) produced by the eruption flares and/or CME-driven shocks propagating from the corona to the interplanetary space. We considered ESP events occurring in association with SEPs on 3 November 2021. We used proton fluxes provided by Solar Orbiter (located at 0.85 AU) in the energy range of 30 keV -82 MeV, by Wind at energies from 70 keV to 72 MeV, and ACE in the range from 40 keV to 5 MeV (both located at the Lagrangian point L1, close to 1 AU along the Sun-Earth direction). In order to broaden the range of analyzed energies (40 keV -72 MeV), we combine these data with the proton fluxes from the SOHO spacecraft, also located at L1. We analyzed the ESP event and fitted the proton energy spectra at both locations with several distributions to shed light on the mechanisms leading to the acceleration of energetic particles.We also investigated the turbulent magnetic field fluctuations around the shock. The obtained ESP spectra, best reproduced by the so-called double power law function, the spectral differences at the two locations, and the shock features (quasi-parallel geometry, enhanced downstream turbulence) suggest that diffusive shock acceleration is responsible for acceleration of low energy particles, whereas stochastic acceleration contributes to the (re) acceleration of high energies ones.